Multicomponent quantitative analysis combined with antioxidant and alpha‐glucosidase inhibitory activities for the quality evaluation of Gastrodia elata from different regions. (28th March 2019) - Gao, Xiaoxiao; Miao, Jing; Guo, Xinhua; Song, Yan; Lv, Tingting; Huang, Luqi; Gao, Wenyuan; Li, Xia
Abstract: Gastrodia elata (G. elata), as a natural plant with nourishing and edible value, plays a vital role in food and pharmaceutical production. In the present study, a novel approach for the simultaneous determination of six components based on high‐performance liquid chromatography (HPLC) coupled with photodiode array detection (PDA) was developed for the quality evaluation of G. elata from different regions. Meanwhile, antioxidant and α ‐glucosidase inhibitory activities were estimated and compared. The results indicated that the total contents of the six compounds in G. elata from Guizhou and Zhejiang provinces obtained by boiling were higher than those obtained by steaming in Anhui and Yunnan provinces. In addition, samples from Guizhou, Yunnan and Shanxi provinces contained more p ‐hydroxybenzyl alcohol, and always possessed higher antioxidant activity, while samples collected from Anhui province showed the highest α ‐glucosidase inhibitory activity with the highest gastrodin content. The results revealed that the quality of G. elata was affected by different regions and different initial processing technologies, which provided a reference for the selection and application of G. elata .